The sesquiterpenes from the stem and leaf of Clausena lansium with their potential antibacterial activities. Issue 23 (2nd December 2021) - Liu, Xin-Yuan; Fu, Xiao-Xiang; Li, Yu-Yan; Xiong, Zhong-Hua; Li, Bao-Tong; Peng, Wen-Wen
Abstract: Two new C13 -norsesquiterpenes claulanterpene A (1 ) and B (2 ), together with two known sesquiterpenes (3–4 ), were isolated from methanol extract of the stem and leaf of Clausena lansium collected from Qingyuan county, Guangdong Province, China. Their structures were elucidated on the base of extensive spectroscopic analysis and comparison with data reported in the literature. Among them, compound 4 showed antibacterial activity against Bacillus cereus . Graphical Abstract: